2021
DOI: 10.1186/s43055-021-00602-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification of COVID-19 pneumonia severity in chest CT using histogram-based multi-level thresholding segmentation

Abstract: Background Chest computed tomography (CT) has proven its critical importance in detection, grading, and follow-up of lung affection in COVID-19 pneumonia. There is a close relationship between clinical severity and the extent of lung CT findings in this potentially fatal disease. The extent of lung lesions in CT is an important indicator of risk stratification in COVID-19 pneumonia patients. This study aims to explore automated histogram-based quantification of lung affection in COVID-19 pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Although the Catphan analysis of CNR showed a significant difference between low-dose protocols and standard acquisitions on both CT scans A and B in the inserts that are closest in HU units to emphysema (Air) or semi-consolidation or consolidation (PMP, LDPE, Polystyrene) as defined by Yousef at al., the clinical relevance of these significant differences was not demonstrated ( 29 ). In fact, the Catphan analysis of CNR is a quick and straightforward measurement that has its limitations and may not be as comprehensive to assess image quality in clinical conditions, which could be brought by other additional metrics such as noise power spectrum, task-based transfer function, or detectability index ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Catphan analysis of CNR showed a significant difference between low-dose protocols and standard acquisitions on both CT scans A and B in the inserts that are closest in HU units to emphysema (Air) or semi-consolidation or consolidation (PMP, LDPE, Polystyrene) as defined by Yousef at al., the clinical relevance of these significant differences was not demonstrated ( 29 ). In fact, the Catphan analysis of CNR is a quick and straightforward measurement that has its limitations and may not be as comprehensive to assess image quality in clinical conditions, which could be brought by other additional metrics such as noise power spectrum, task-based transfer function, or detectability index ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, semi-quantitative visual assessment highly relies on the experience of the observer. It is time-consuming, lacks reproducibility, and has interobserver and even intraobserver variability ( 15 ). For the longitudinal study in this work, semi-quantitative methods may significantly affect the accuracy and feasibility of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CT has been proposed as an ancillary approach for screening individuals with suspected COVID-19 pneumonia during the epidemic period and monitoring treatment response according to the dynamic radiological changes (12)(13)(14). Traditional CT image analysis methods such as manual or semiquantitative assessments rely on the previous experience of radiologists, and these methods are subjective, time-consuming, and lack interobserver consistency (15,16). As a fast, accurate and reproducible analytical tool, quantitative CT image analysis has been increasingly implemented in pulmonary diseases to extract objective data that can aid in lesion characterization and quantification (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Radiology (ACR) recommends the use of computed tomography for suspected COVID-19 infection (21). However, visual assessment of COVID-19 lesions from chest CT scans is time-consuming, suffers from inter-and intra-reader variability, and lacks reproducibility (22) Neither of these two studies reported the MAE for their algorithms. In a deep learning task with numerical outcomes, MAE provides a notion of how much the results will vary in clinical settings.…”
Section: Discussionmentioning
confidence: 99%